Employees performances at the palm oil factory: A Fundamental study - Saleh, H. (International Journal of Human and Technology Interaction (IJHaTI), 2021)
The present study investigate the palm oil factory employee performance at Pahang Malaysia. It was found that personal motivation, remuneration, and training was an important factor to determine the employees’ performance, but work environment was rejected. The finding of this study is important and make an additional information for employers to motivate employees and develop effective ways to improve employees’ performance in order to grow the palm oil manufacturing industry through creating a good relationship between management and operations staff. This is essential because employee is the most valuable asset for an organization to be successful and highly productivity can only be achieved through excellent employee performance